Communication strategies in english as a lingua franca transcultural communication - Antonello, Monica (Cambridge Scholars Publishing, 2023)
English as a Lingua Franca (ELF) Transcultural Communication acknowledges the interconnection between language and culture in intercultural contexts, where the sharing of linguistic and cultural norms and practices cannot be taken for granted. This book suggests ‘ELF Transcultural Competence’ as an alternative model of skills that are needed to be successful communicators in such contexts. Moreover, it explores the important role of communication strategies and meaning negotiation in ELF transcultural contexts, focusing on both qualitative and quantitative analysis. It also introduces some practical examples of how to include such issues in an ELF-aware pedagogy that could be of particular interest for teachers, teacher educators and researchers
9781527593992
Keywords: Fremdsprachenerwerb und -didaktik; Englisch; Mehrsprachigkeit; Interkulturelle Kommunikation & Interaktion; Language and Linguistics